Childfree Paradigm Builds New Perspective - Mahmudin Bunyamin; Agus Hermanto; Rohmi Yuhani’ah; Iwannudin; Habib Ismail (International Journal of Community Engagement Payungi, 2025)
In classical fiqh studies, scholars agree that having children is a desired outcome of marriage. However, in modern times, the promotion of the childfree lifestyle is increasingly advocated through scientific discourse. The question arises: what factors contribute to childfree becoming a goal of marriage, and what is the contribution of this research to the renewal of contemporary Islamic family law? The purpose of this research is to challenge societal paradigms about childfree and work towards building a new perspective as part of the renewal of contemporary Islamic family law. This research is a field study (field research) in the form of qualitative research with a socio-psychological approach using the iceberg theory. Data was collected through interviews with respondents, specifically from the younger generation. The results of the study indicate that the childfree paradigm exists because it is promoted through mass media, print media, scientific articles, and other scholarly discussions that deliberately instill the idea that childfree is a lifestyle choice. The researcher suggests that education on this matter should be provided by various parties, including religious leaders through organizations, religious counselors, health professionals, as well as psychologists and psychiatrists, to build a perspective that having children is one of the main purposes of marriage.